Penerapan Algoritma Titik Interior dalam Optimasi Keuntungan pada Toko Churro.io - Alivia Tasya Kemala; Rara Sandhy Winanda (Journal of Mathematics UNP, 2023)
Linear Programming is a part of optimization. One of the methods that can be used to solve linear programming problems is the interior point algorithm method. This research is an applied research was aimed to apply the interior point algorithm to solved production optimization problems at Churro.io. The data collection method used in this research was an interview by researcher with Churro.io’s owner. Based on the results of the research using the calculation of the interior point algorithm, a maximum profit of Rp 1.216.400 was obtained by producing 60 units of dark chocolate royal churro, 37 units of white chocolate royal churro, 33 units of matcha royal churro, 21 units of tiramisu royal churro, 21 units of salted caramel royal churro, and 14 units of cheese royal churro. The profit was obtained by Churro.io’s calculation of Rp 890.500, so there is a difference between the calculation of the interior point algorithm and the calculation at the Churro.io of Rp 325.900.